2007
DOI: 10.1044/1092-4388(2007/081)
|View full text |Cite
|
Sign up to set email alerts
|

Analogous and Distinctive Patterns of Prelinguistic Communication in Toddlers With and Without Hearing Loss

Abstract: Purpose: This study was conducted to compare the prelinguistic communicative abilities of toddlers with hearing loss and without hearing loss during the 2nd year of life and shortly before the emergence of productive single-word lexicons. Method: The participants were 28 toddlers with hearing loss who participated in an early intervention program and 92 toddlers with normal hearing at similar language levels and close chronological ages. The assessment consisted of the Hebrew Parent Questionnaire-Communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…Recent research utilizing both parental report and videotaped analyses during parent–child interactions provides us with some limited applications in terms of JBR and young children with HL (Cruz, Quittner, Marker, & DesJardin, 2013; DesJardin & Eisenberg, 2007; Fung, Chow, & McBride-Chang, 2005; Zaidman-Zait & Dromi, 2007). Most of the cited research has been conducted on preschool to early childhood populations of children who have severe to profound HL, and two investigations included children who utilize cochlear implants.…”
Section: Children With Hlmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research utilizing both parental report and videotaped analyses during parent–child interactions provides us with some limited applications in terms of JBR and young children with HL (Cruz, Quittner, Marker, & DesJardin, 2013; DesJardin & Eisenberg, 2007; Fung, Chow, & McBride-Chang, 2005; Zaidman-Zait & Dromi, 2007). Most of the cited research has been conducted on preschool to early childhood populations of children who have severe to profound HL, and two investigations included children who utilize cochlear implants.…”
Section: Children With Hlmentioning
confidence: 99%
“…Utilizing a parental observation questionnaire, which measured the frequency of parent–child storybook reading and child linguistic production, toddlers with HL demonstrated lower spontaneous use of words and reduced involvement in JBR with their parents compared to toddlers with NH. Reduction in hearing may impede the coordination between adult, child, and object in toddlers with HL due to a need to alternate gaze between parent and book to receive the linguistic information from the parent (Zaidman-Zait & Dromi, 2007). …”
Section: Children With Hlmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of presymbolic communication has been described for individuals with different types of disabilities and disorders including hearing impairment (Zaidman-Zait & Dromi, 2007), brain lesions (Bates, Vicari, & Trauner, 1999), autism (Luyster, Qiu, Lopez, & Lord, 2007; Chian, Soong, Lin, & Rogers, 2008; Wetherby, et al, 2004), Down syndrome (Abbeduto, Warren, & Conners, 2007; Fidler, Philofsky, Hepburn, & Rogers, 2005), Williams syndrome (Singer-Harris, Bellugi, Bates, Jones, & Riossen, 1997), Angelman syndrome (Didden et al, 2009) and fragile X syndrome (Flenthrope & Brady, 2010). For example, children with Down syndrome typically have a profile of relative strength in gesture use across communicative functions (Abbeduto et al, 2007; Brady et al, 2008) whereas children with autism frequently have an uneven profile characterized by infrequent commenting gestures (Anderson et al, 2007; Kasari, Freeman, & Paparella, 2006)…”
mentioning
confidence: 99%
“…Research on SBR is sparse for infants and toddlers with HL who are fitted with hearing aids (DesJardin et al, 2014; Zaidman-Zait & Dromi, 2007). In terms of frequency of book reading, in a recent cross-sectional study, DesJardin and her colleagues (2014) found no significant group differences for parental perceptions of frequency of reading at home (i.e., number of minutes per day) between parents of young children with HL (mean age = 25.8 months) and parents of a NH control group (mean age = 18.6 months), even after controlling for children's age.…”
Section: Introductionmentioning
confidence: 99%